O BancoSol, do microcrédito a banco comercial: singularidades das microfinanças na Bolívia - Wochler, Regiane Vieira (2009)
The BancoSol of Bolivia, one of the leading microfinance organizations in Latin America since its inception in 1986 became one of the largest commercial banks in the country from the early years of the century XXI. Although presented today as an IMF, the BancoSol is actually one of largest commercial banks in the country, alongside Banco Los Andes, who was also an IMF in its origin, in other words, the Bolivian commercial banking system today existing was developed from microfinance organizations. This dissertation argues that this unusual configuration happened due to the weakening of the traditional banking system with the serious financial crises of the 1980s, amid the severe social effects of economic instability and disruption of the production structure that marked this period. This study examines changes in BancoSol toward to the profile of a commercial bank, through literature and documents, making it difficult to obtain information about its history, despite the importance attributed to him by the literature on microfinance